Невербальные средства в педагогическом общении - Снегурова, Татьяна Алексеевна (Видавничий дім "Гельветика", 2020)
Исследование невербальной коммуникации занимает особое место в литературе по педагогической психологии. Ученые разных стран изучают проявление эмоций, взгляд, изменение ритма и тона голоса, жесты, позы, межличностное пространство и другие каналы невербальной коммуникации у представителей разных культур с целью совершенствования учебного процесса. Однако во многих учебниках по психологии доминирующая роль отводится вербальной сфере, на которую направлено основное внимание. В результате перехода от линейной модели коммуникации к диалого-интерактивной, в которой коммуникация представлена как продукт совместной активности собеседников по производству значения, разница между вербальной и невербальной коммуникацией практически исчезла.

The article is devoted to the problem of using non-verbal means in pedagogical interaction of teacher and students. The theoretical basis of the study is the thesis as following: as a result of the transition from a linear model of communication to a dialogue-interactive model, the difference between verbal and non-verbal communication has virtually disappeared. That is why it is very important to take into account the differences in the means of non-verbal communication between teachers and students and between students from different cultural backgrounds because they can be communication barriers during educational activities. The article considers such components of non-verbal communication as posture, gestures, look, interpersonal distance, etc. Their use is greatly influenced by the cultural norms of the countries from which students come to study. These norms often differ from each other and do not always correlate with those existing in Ukraine. The article presents various situations of intercultural misunderstanding. So, for example, depending on the cultural norms accepted in a native society, one of interlocutors can break interpersonal distance at conversation; therefore, there is an inconvenience in relations of communicators. This violation is especially painful when communicating with unequal interlocutors. The author focuses on an important variable that regulates the relationship between teacher and students – the spatial location of students in relation to the teacher’s desk. In addition, it is emphasized that the organization of class life is strongly influenced by the movements of the teacher. With the help of movements, the teacher manages the physical contacts, orientation, and postures of students and therefore, forms the systems of interaction possible in the classroom. And the last thing that is discussed in the article is the position of the body that a person (consciously or unconsciously) holds: position of domination or subordination. Recommendations on which pose should be used by the teacher when explaining the material and when interviewing students are given. The author concludes that when working with international students, the teacher must take into account the differences in communicative non-verbal signals that are inherent in different cultures. It is emphasized that even a minor violation of socio-cultural norms established in a particular cultural area can disorganize the process of pedagogical communication.
Non-verbal means in pedagogical communication
Keywords: культурные нормы; межличностная дистанция; поза; жесты; учебный процесс; non-verbal means of communication; posture; gestures; interpersonal distance; pedagogical interaction; cultural norms